Two-faced Janus: on the 150th anniversary of the discovery of DDT - O. V. Morozova; A. Yu. Bukina; V. G. Popova; G. I. Khairieva; G. R. Sagitova; G. A. Belitsky; M. G. Yakubovskaya; K. I. Kirsanov; V. P. Maksimova (Успехи молекулярной онкологии, 2024)
One of the factors associated with increased morbidity of malignant neoplasms is environmental pollution with cancerogenic compounds including pesticides. Until recently, stable organic pollutant insecticide dichlorodiphenyltrichloroethane (DDT) was the single tool for fighting malaria carriers. Despite vast evidence of its negative effect on human health, DDT is still used in some countries.Aim. To perform a comprehensive analysis of the dynamics of DDT pesticide use and the consequences of its use on the global healthcare as well as to investigate the mechanism of its action on the human body including the endocrine system and cancerogenic effects.The review was composed using the PubMed (2853 publications), Elsevier (3139 publications), eLibrary (784 publications) biomedical literature databases. Full-text articles were retrieved through PubMed Central (PMC), Science Direct, Research Gate, CyberLeninka electronic resources.